About the Portrait of V. V. Stasov by I. Yu. Repin from the Collection of the Kharkiv Art Museum - Shilo, Alexander; Tymofieieva, Nataliia; Pianyda, Yurii (HUDPROM: The Ukrainian Art and Design Journal, 2023)
In 1907, the collection of the Kharkiv Art and Industrial Museum received a portrait of V. V. Stasov from the author. The portrait was written by I. Repin in 1905 in Penaty. This was the last portrait of Stasov, created by Repin from life. A portrait from Kharkiv collection completes the series, which includes several pictorial images. These are portraits of 1873; 1883, created in Dresden during a joint trip of the artist and critic to Europe; 1889–1890 – in a red shirt; 1900 – in a fur coat. It is worth noting that out of five picturesque portraits, three are costumed, specially conceived as “portraits with disguises”. Why did the artist need this masquerade? What does this portrait say about Repin’s personality and Repin’s work? The history of the creation of this portrait is considered in two contexts: firstly, those artistic tasks that the artist solved in the whole series of the mentioned images of the critic; secondly, in the biographical context of the relationship between the artist and the critic for more than thirty years. It is shown how, from the first to the last portrait, the trajectory of the artist’s exit from the influence of the critic’s ideas and his acquisition of his own views on art is outlined. In accordance with this, the composition of the work changed from portrait to portrait, in which the artist’s arbitrariness in solving the image of the critic is increasingly manifested. Deciding on the composition of each of the portraits, Repin at least demonstrates how in his work there was a transition from complete immersion in the content of the critic’s monologue to their dialogic relationship and departure from Stasov’s postulates as his own artistic worldview was formed. The authors defend the point of view on the portrait of Stasov from the collection of Kharkiv Art Museum as an outstanding work of the late period of I. Yu. Repin, who still needs to be deeply researched.